Outcomes Following Treatment of Symptomatic Accessory Navicular with Pes Planus Correction: A Systematic Review - Thelma R. Jimenez Mosquea MD; Hugo A. Ubillus MD; Raymond J. Walls MD, FRCS (Orth), MFSEM, FAAOS (Foot & Ankle Orthopaedics)
Category: Midfoot/Forefoot; Other Introduction/Purpose: The presence of an accessory navicular (AN) can disrupt the attachment of the tibialis posterior tendon (TPT), potentially resulting in a flattened medial longitudinal arch. The Kidner procedure aims to alleviate painful AN by correcting the abnormal TPT insertion, thus aiding in arch elevation. Subtalar arthroeresis (STA) serves to prevent excessive subtalar joint eversion, thereby averting arch collapse in flatfoot deformity. Conversely, the addition of a medial column reinforcement through osteotomy has been proposed to further stabilize the corrected foot shape. Literature on AN treatment often overlooks options for flatfoot deformity. This study compares outcomes of Kidner alone, Kidner with STA, and Kidner with medial column reinforcement for symptomatic AN with flatfoot, seeking to provide valuable treatment insights. Methods: In February 2024, a systematic review was conducted on the PubMed, Embase, and Cochrane Library databases to identify clinical studies investigating outcomes of the Kidner procedure alone, Kidner with STA, and Kidner with osteotomies for managing symptomatic accessory navicular (AN) with flatfoot deformity. The level of evidence (LoE) in the included studies was assessed according to the criteria set by the Journal of Bone and Joint Surgery. Information pertaining to subjective clinical outcomes, radiological findings, and complications was gathered and subjected to analysis. Results: This review included 19 studies, comprising one with Level II evidence, thirteen with Level III, and five with Level IV. Among 525 cases, 246 underwent Kidner procedure, 166 the Kidner + STA and 113 the Kidner + medial osteotomy. The weighted mean age was 15.7 ± 3.9 years for the Kidner cohort, 12.4 ± 2.7 years for the Kidner + STA and 25.29 ± 12.1 years for the Kidner + osteotomy, with weighted-mean follow-up of 67.8, 44.06 and 25.01 months, respectively. Pre-operative AOFAS mean scores were 46.0, 56.4 and 52.8, with post-operative scores of 85.5, 89.7 and 89.7, respectively. At final follow-up, Meary’s angle improved 0.7 degrees in the Kidner, 13.2 degrees in the Kidner + STA and 10.86 degrees in Kidner + osteotomy. Conclusion: This review highlights the effectiveness of different procedures in managing symptomatic accessory navicular with flatfoot deformity. The three approaches demonstrated improvements in subjective clinical outcomes and radiological parameters. Kidner alone experienced less radiologic improvement, suggesting that augmentation with either STA or osteotomy may provide better correction. Despite limitations in study design and heterogeneity among included studies, our findings underscore the importance of individualized treatment approaches. Further research with larger sample sizes and longer follow-up periods is warranted to validate these findings and optimize treatment strategies for this challenging condition.